Public policy in poverty reduction study of implementation BLT program in West Pasaman District - Sonda Winari; Aldri Frinaldi; Syamsir Syamsir (Enrichment : Journal of Management, 2023)
The problem of poverty is a serious problem for a government, both the central government and the district government. Poverty reduction has a strategic role in efforts to accelerate poverty reduction in an area. One of the government's efforts to reduce poverty in Indonesia is in West Pasaman district, namely by implementing the Direct Cash Assistance (BLT) program based on Presidential Instruction No. 3 of 2008 dated May 14, 2008. Poverty is also defined as a condition where one's basic needs are not fulfilled. The problem of poverty is a very complex and multidimensional problem. Therefore, poverty alleviation efforts must be carried out in a comprehensive manner and cover various aspects of life and be implemented in an integrated manner. In accordance with what was described above, the purpose of this study was to find out the extent to which the West Pasaman Regency government's policies are in tackling poverty, one of which is by distributing Direct Cash Assistance (BLT).